A New Duplication Task Scheduling Algorithm in Heterogeneous Distributed Computing Systems - Aida A Nasr; Nirmeen A EL-Bahnasawy; Ayman EL-Sayed (Institute of Advanced Engineering and Science, 2016)
The efficient scheduling algorithm is critical to achieve high performance in parallel and distributed systems. The main objective of task scheduling is to assign the tasks onto the available processors with the aim of producing minimum schedule length and without violating the precedence constraints. So we developed new algorithm called Mean Communication Node with Duplication MCND algorithm to achieve high performance task scheduling. The MCND algorithm has two phases namely, task priority and processor selection. Our algorithm takes into account the average of parents' communication costs for each task to reduce the overhead communication. The algorithm uses new task duplication algorithm. We build a simulation to compare the MCND algorithm with CPOP with duplication algorithm. The algorithms are applied on real application. From results, the MCND algorithm shows the best results